ANALYSIS OF THE ROLE OF THE BRCA1 AND BRCA 2 GENES AS A PREDICTOR OF OVARIAN CANCER. PREVALENCE OF OVARIAN CANCER IN THE REPUBLIC OF UZBEKISTAN - Iroda A.Kamilova; Shirina A. Valijonova (Scholar Express Journals, 2023)
According to the World Health Organization, ovarian cancer accounts for 4-6% of malignant tumors in women and ranks seventh in frequency. According to the International Agency for Research on Cancer, more than 165 thousand new cases of ovarian cancer are registered annually in the world, and more than 100 thousand women die from malignant ovarian tumors. If the proportion (%) of ovarian cancer in the oncological incidence of women in all countries of the world is approximately the same, then the incidence rate per 100 thousand female population (%) is significant. To date, the contingent of patients with malignant neoplasms in the Republic of Uzbekistan, namely with ovarian cancer, is 4.2%. Despite the improvement of diagnostic methods, the provision of modern medical equipment, the introduction of screening programs, the proportion of actively diagnosed patients, as well as patients with stages 1 and 2 of the tumor process, remains quite low, in particular with visual malignant neoplasms.
Keywords: ovarian cancer; incidence of rural and urban population; Uzbekistan